Translational research on esophageal adenocarcinoma: from cell line to clinic. Issue 1 (24th June 2013) - Boonstra, J. J.; Tilanus, H. W.; Dinjens, W. N. M.
Summary Human esophageal adenocarcinoma (EAC) cell lines have made a substantial contribution to elucidating mechanisms of carcinogenesis and drug discovery. Model research on EAC relies almost entirely on a relatively small set of established tumor cell lines because appropriate animal models are lacking. Nowadays, more than 20% of all fundamental translational research studies regarding EAC are partially or entirely based on these cell lines. The ready availability of these cell lines to investigators worldwide have resulted in more than 250 publications, including many examples of important biomedical discoveries. The high genomic similarities (but certainly not completely identical) between the EAC cell lines and their original tumors provide rational for their use. Recently, in a collaborative effort all available EAC cell lines have been verified resulting in the establishment of a reliable panel of 10 EAC cell lines. It could be expected that the value of these cell lines increases as unlimited source of tumor material because new biomedical techniques require more tumor cells and the supply of viable tumor cells is diminishing because of neoadjuvant chemo(radio)therapy of patients with EAC. Here, we review the history of the EAC cell lines and their utility in translational research and biomedical discovery.